2007
DOI: 10.1007/s00705-007-1035-9
|View full text |Cite
|
Sign up to set email alerts
|

Varying genetic diversity of Papaya ringspot virus isolates from two time-separated outbreaks in Jamaica and Venezuela

Abstract: Coat protein sequences of 22 Papaya ringspot virus isolates collected from different locations in Jamaica and Venezuela in 1999 and 2004, respectively, were determined and compared with sequences of isolates from earlier epidemics in 1990 and 1993. Jamaican isolates collected in 1999 exhibited nucleotide sequence identities between 98 and 100% but shared lower identities of 92.2% with an isolate collected in 1990. Isolates from the 2004 epidemic in Venezuela exhibited more heterogeneity, with identities betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Similarly to Indian isolates, Puerto Rican isolates grouped independently of their geographical origin, although a higher level of conservation was observed among the latter isolates (Zambrana-Echevarr ıa et al, 2016). In this work, genetic variation was detected between isolates collected from the same areas (Boyeros-1 and -2, Melena del Sur-1 and -2, Santo Domingo-1 and -2), on different collection dates (2-6 years), which coincided with observations of Chin et al (2007). These authors analysed sequences collected from Jamaica and Venezuela in different periods and associated the variability with the movement of germplasm and the implemented management practices.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Similarly to Indian isolates, Puerto Rican isolates grouped independently of their geographical origin, although a higher level of conservation was observed among the latter isolates (Zambrana-Echevarr ıa et al, 2016). In this work, genetic variation was detected between isolates collected from the same areas (Boyeros-1 and -2, Melena del Sur-1 and -2, Santo Domingo-1 and -2), on different collection dates (2-6 years), which coincided with observations of Chin et al (2007). These authors analysed sequences collected from Jamaica and Venezuela in different periods and associated the variability with the movement of germplasm and the implemented management practices.…”
Section: Discussionsupporting
confidence: 61%
“…In this work, genetic variation was detected between isolates collected from the same areas (Boyeros‐1 and ‐2, Melena del Sur‐1 and ‐2, Santo Domingo‐1 and ‐2), on different collection dates (2–6 years), which coincided with observations of Chin et al . (). These authors analysed sequences collected from Jamaica and Venezuela in different periods and associated the variability with the movement of germplasm and the implemented management practices.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The results based on the CP nucleotide sequences also showed that the isolates were distributed into different groups according to the region of origin. Chin et al [33] also detected a high genetic variability among the PRSV isolates from Venezuela compared to isolates from Jamaica. Such differences could be related, among other factors, to geographic isolation [34].…”
Section: Resultsmentioning
confidence: 94%
“…ns, non-significant; **significant (P < 0AE01). (Azzam et al, 2000;Bateson et al, 2002;Chin et al, 2007). It should be noted that the genetic flow between Andalucía and surrounding areas may be strongly constrained by mountain barriers.…”
Section: Discussionmentioning
confidence: 99%